Prevalence and Health Outcomes of Functional Gastrointestinal Symptoms in Infants From Birth to 12 Months of Age - Vandenplas, Yvan (J Pediatr Gastroenterol Nutr, 2015)
OBJECTIVES: The aim of the study was to review published evidence and the opinion of practising clinicians on the prevalence and long-term health consequences of functional gastrointestinal symptoms in infants younger than 12 months. METHODS: PubMed was searched from inception to November 2014 to find articles reporting the prevalence and long-term health outcomes of infantile colic, regurgitation, functional constipation, functional diarrhoea, and dyschezia in infants younger than <12 months. A questionnaire was sent to practising clinicians worldwide, and a group of 15 international experts met to discuss the likely frequency and longer-term consequences of these symptoms. RESULTS: The literature search identified 30 studies reporting the prevalence of infantile colic (2%–73%), 13 that of regurgitation (3%–87%), 8 that of functional constipation (0.05%–39.3%), 2 that of functional diarrhoea (2%–4.1%), and 3 that of dyschezia (0.9%–5.6%). The studies varied in design, populations investigated, and definition of the symptoms. Questionnaires were received from 369 respondents. The experts agreed that the likely prevalences for colic, regurgitation, and functional constipation were 20%, 30%, and 15%, respectively. The limited data in the literature for functional diarrhoea and dyschezia suggest prevalences <10%. Infantile colic may be associated with future health problems in a subset of infants. CONCLUSIONS: Functional gastrointestinal symptoms appear to occur in a significant proportion of infants younger than 12 months and may have an impact on future health outcomes. Prospective collection of data according to agreed criteria is needed to obtain more accurate estimates of the prevalence and consequences of these symptoms.